Principle of Educational Training and Requirements to Organizations Educational Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes implementation of the principle of educational training. Fundamentality in teaching presupposes scientific character, completeness and depth of knowledge. It is due to the nature of the modern scientific and technological revolution, which requires a person to have highly intellectual mobility, a research mindset, the desire and ability to constantly replenish their knowledge as changes occur in life and activity.